2023
DOI: 10.1071/mf22263
|View full text |Cite
|
Sign up to set email alerts
|

Multi-gene insights into the taxonomy and conservation of Tasmania’s galaxiid fishes

Abstract: Context Galaxiids are a widespread, southern hemisphere, radiation of mostly obligate freshwater fishes. Tasmania houses a diversity of endemic species of Galaxias and Paragalaxias. Of these, many are at risk of extinction, being landlocked, range-restricted and subject to anthropogenic threats, placing a high-conservation priority on the region. Aim Our aim was to synthesise historic and published molecular datasets to provide the sound systematic framework needed to underpin future conservation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Phylogeographic assessments of freshwater fishes have commonly revealed cryptic species (e.g., Adams et al, 2014;Baumsteiger et al, 2012;Pinacho-Pinacho et al, 2018), thereby improving knowledge of species richness and diversity in aquatic ecosystems globally (Seehausen & Wagner, 2014). In Australia, for example, the number of recognized (but not necessarily described) species increased by 39 between 2002 and 2013 (Allen et al, 2002;Unmack, 2013), with many of the newly defined species revealed by molecular phylogenetic and phylogeographic evidence (Adams et al, 2023). Furthermore, phylogeographic studies have indicated that historical, geological, and/or climatic processes can be determinants of contemporary patterns of biodiversity and distribution across riverine landscapes (e.g., Buckley et al, 2021;Shelley et al, 2020;Waters et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogeographic assessments of freshwater fishes have commonly revealed cryptic species (e.g., Adams et al, 2014;Baumsteiger et al, 2012;Pinacho-Pinacho et al, 2018), thereby improving knowledge of species richness and diversity in aquatic ecosystems globally (Seehausen & Wagner, 2014). In Australia, for example, the number of recognized (but not necessarily described) species increased by 39 between 2002 and 2013 (Allen et al, 2002;Unmack, 2013), with many of the newly defined species revealed by molecular phylogenetic and phylogeographic evidence (Adams et al, 2023). Furthermore, phylogeographic studies have indicated that historical, geological, and/or climatic processes can be determinants of contemporary patterns of biodiversity and distribution across riverine landscapes (e.g., Buckley et al, 2021;Shelley et al, 2020;Waters et al, 2020).…”
Section: Introductionmentioning
confidence: 99%